Community Perceptions About the Development of Sustainable Pasir Jambak Beach Tourism Objects - Okriyeni Sudiar; Zulhendra Syafardi; Septian Budiman; Abdul Razak (Journal of Climate Change Society, 2023)
In developing beach tourism objects, of course there is the role of the community as a successor for the development of Pasir Jambak beach. Community understanding regarding environmental conditions in the presence of tourist objects will certainly provide a tourist attraction that will not damage the environment. This study aims to determine the views/perceptions of the community regarding the development of sustainable Pasir Jambak Beach Tourism objects. This research is descriptive qualitative. In this study, the research informants consisted of the community around Pasir Jambak beach. The sampling technique was carried out using the Snowball Sampling technique. Data collection techniques used are interview techniques and observation techniques. The data analysis technique used is analysis based on the data obtained, then developed into a hypothesis. The community is very concerned about the sustainable development of Pasir Jambak Beach by keeping the beach clean, erecting buildings that do not damage the beach environment, not cutting down pine trees and not doing activities that can cause beach abrasion.